Melatonin Synergizes With Mesenchymal Stromal Cells Attenuates Chronic Allograft Vasculopathy - Qin, Ya-fei; Kong, De-jun; Qin, Hong; Zhu, Yang-lin; Li, Guang-ming; Sun, Cheng-lu; Zhao, Yi-ming; Wang, Hong-da; Hao, Jing-peng; Wang, Hao (Frontiers in Immunology, 2021)
Background: Chronic rejection characterized by chronic allograft vasculopathy (CAV) remains a major obstacle to long-term graft survival. Due to multiple complicated mechanisms involved, a novel therapy for CAV remains exploration. Although mesenchymal stromal cells (MSCs) have been ubiquitously applied to various refractory immune-related diseases, rare research makes a thorough inquiry in CAV. Meanwhile, melatonin (MT), a wide spectrum of immunomodulator, plays a non-negligible role in transplantation immunity. Here, we have investigated the synergistic effects of MT in combination with MSCs in attenuation of CAV. Methods: C57BL/6 mouse recipients receiving BALB/c mouse donor aorta transplantation have been treated with MT and/or adipose-derived MSCs. Graft pathological changes, intragraft immunocyte infiltration, splenic immune cell populations, circulating donor-speciﬁc antibodies levels, cytokine profiles were detected on post-operative day 40. The proliferation capacity of CD4+ and CD8+ T cells, populations of Th1, Th17, and Tregs were also assessed in vitro. Results: Grafts in untreated recipients developed a typical pathological feature of CAV characterized by intimal thickening 40 days after transplantation. Compared to untreated and monotherapy groups, MT in combination with MSCs effectively ameliorated pathological changes of aorta grafts indicated by markedly decreased levels of intimal hyperplasia and the infiltration of CD4+ cells, CD8+ cells and macrophages, but elevated infiltration of Foxp3+ cells. MT either alone or in combination with MSCs effectively inhibited the proliferation of T cells, decreased populations of Th1 and Th17 cells, but increased the proportion of Tregs in vitro. MT synergized with MSCs displayed much fewer splenic populations of CD4+ and CD8+ T cells, Th1 cells, Th17 cells, CD4+ central memory T cells (Tcm) as well as effector memory T cells (Tem) in aorta transplant recipients. In addition, the percentage of splenic Tregs was substantially increased in the combination therapy group. Furthermore, MT combined with MSCs markedly reduced serum levels of circulating allospecific IgG and IgM, as well as decreased the levels of pro-inflammatory cytokines, but increased the level of IL-10 in the recipients. Conclusions: These data suggest that MT has synergy with MSCs to markedly attenuate CAV and provide a novel therapeutic strategy to improve the long-term allograft acceptance in transplant recipients.